EXHAUSTIVE EXTRACTION AND SCREENING THE BIOLOGICAL ACTIVITIES OF HELIOTROPIUM HIRSUTISSIMUM (HAIRY HELIOTROPE): A MEMBER OF PALESTINIAN FLORA - Jaradat, Nidal; Salahat, Ala’ Khader Isa; Abu-hadid, Mahmoud (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: Heliotropium hirsutissimum Grauer. is one of the important folk plants that grow wildly in the mountains of Palestine and widely used for several purposes by tribal peoples and traditional practitioners for treatment of various skin inflammations as a paste, for that our study aimed to evaluate antibacterial and antifungal activities for this plant. Methods: In our experiments, the entire plant exhaustively extracted by n-hexane and ethanol mixed with an equal volume of triple distilled water to yield 2.36 g crude aqueous extract and 0.42 g crude organic extract from 25 g of the plant and then screened for antifungal and antibacterial activities. Results: The plant aqueous extract showed antibacterial activities against all Gram-positive bacteria with the greatest activity against Staphylococcus epidermidis, its inhibition zone diameter (DIZ) was 16 mm equivalent to 50% of the DIZ of imipenem a broad spectrum antibiotics. Furthermore, the plant aqueous extract activity against Bacillus subtilis and Staphylococcus aureus were 21.7% of imipenem activity (10 mm) and 26% imipenem activity (12 mm), respectively. The minimum inhibition concentration (MIC) of the aqueous extract was 30 mg/ml or less against all bacterial strains as well as against the fungi Candida albican. More specifically, the MIC ranged between 2.7 mg/ml and 30 mg/ml with the lowest MIC value was 2.7 mg/ml against S. epidermidis, while Pseudomonas aeruginosa, Escherichia coli, and C. albican was all inhibited at the highest concentration of 30 mg/ml. There is no bacteriocidal or fungicidal effect of its extract at 30 mg/ml the highest concentration tested in our experiments. The organic extract showed identical antibacterial activity of aqueous extract except in that it had no activity against B. subtilis, as well as it had antibacterial activity against E. coli with DIZ of 50% of DIZ of imipenem (18 mm) and antifungal activity against C. albican with DIZ 80% of DIZ of nystatin broad spectrum antifungal compound (16 mm). Conclusion: The plant aqueous and organic extracts have antibacterial, antifungal active compounds. Keywords: Heliotropium hirsutissimum, Antibacterial, Antifungal, Hairy heliotrope.